2020
DOI: 10.3390/ijerph17124544
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Internet-Based Program to Promote Physical Activity and Exercise after Inpatient Rehabilitation in Persons with Multiple Sclerosis: A Randomized, Single-Blind, Controlled Study

Abstract: Background: Multimodal rehabilitation improves fatigue and mobility in persons with multiple sclerosis (PwMS). Effects are transient and may be conserved by internet-based physical activity promotion programs. Objective: Evaluate the effects of internet-based physical activity and exercise promotion on fatigue, quality of life, and gait in PwMS after inpatient rehabilitation. Methods: PwMS (Expanded Disability Status Scale (EDSS) ≤ 6.0, fatigue: Würzburg Fatigue Inventory for Multiple Sclerosis (WEIMuS) ≥ 32) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
0
20
1
1
Order By: Relevance
“…We believe that these efforts have succeeded during the COVID-19 pandemic in motivating a large segment of PwMS to maintain their PA habits, despite the lockdown conditions. An additional explanation might involve the rapid development and use of digital applications promoting PA, including applications specifically addressed to PwMS ( Dennett et al, 2018 , Remy et al, 2020 , Flachenecke et al, 2020 ). Recently Remi et al (2020) investigated the compliance of PwMS in using telecommunication technologies for rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that these efforts have succeeded during the COVID-19 pandemic in motivating a large segment of PwMS to maintain their PA habits, despite the lockdown conditions. An additional explanation might involve the rapid development and use of digital applications promoting PA, including applications specifically addressed to PwMS ( Dennett et al, 2018 , Remy et al, 2020 , Flachenecke et al, 2020 ). Recently Remi et al (2020) investigated the compliance of PwMS in using telecommunication technologies for rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Remi et al (2020) investigated the compliance of PwMS in using telecommunication technologies for rehabilitation. The authors found that 62% of the cohort was interested in receiving physical exercise program, and 69% were interested in information and personalized advice about PA and MS ( Flachenecke et al, 2020 ). Although, access to these technologies was not feasible for all PwMS, there was a possibility that a relatively large portion of patients benefited from these novel technologies during the lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty studies about the use of mHealth for rehabilitation interventions of pwMS were included in this review, representing a total of 1962 patients [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The majority of these studies ( n = 25; 3%) were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneity between the studies, and the patients, makes it more difficult to compare studies and especially to generalize the results. A second important limitation is that most of the included studies on the rehabilitation aspects (except [32,35,38,40,45]) have relatively small sample sizes and the results are likely to be underpowered [72]. Furthermore, the percentage of participants that were included in the final analysis is 90% and information about the adherence to the intervention was missing (usually a threshold of 80% is applied to determine if the participants do a sufficient amount of exercises [73]).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the included RCTs, 20 were included in the meta-analysis assessing the efficacy of mHeath for rehabilitation [24,[26][27][28][29][30][31][33][34][35][36][37]39,40,44,45,[47][48][49]51,65], representing 1,393 pwMS. When considering all the studies and ICF domains together, the heterogeneity between the studies was moderate (tau 2 = 0.30, 95%CI [0.26; 0.62]), therefore we decided to use random-effect model.…”
Section: Rehabilitationmentioning
confidence: 99%